Optical Transient Suppression using Stimulated Raman Attenuation - Holtmannspötter, Michael; Stephan, C.; Onishchukov, Georgy; Leuchs, Gerd; Schmauß, Bernhard (ECOC, September, 2008)
Dynamic optical attenuation based on the Raman Effect is investigated experimentally. The suppression of optical power transients as they arise from dynamic processes of EDFAs is shown. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.optica_3